THE IMPORTANCE OF CAPITAL MARKETS IN THE DEVELOPMENT OF REAL ESTATE SECTOR - Resül YAZICI (Fırat University, 2019)
In Turkey, various factors such as the height of the inflation rate and the pressure of the current account deficit on the exchange rate affects the internal and external value of money negatively. For such reasons in an environment experiencing short term behaviour the pessimism of the saving owner and the investors causes them not to turn to long-term markets, ie capital markets. Moreover, because some segments have an interest anxiety, this leads to the formation of mattress savings in gold or foreign currency. Without imparting to the financial system ie economy, savings accumulating in this way are transformed into reel assets when a certain figure is reached. For example, when the value of mattress savings such as gold or foreign exchange reaches a certain figure first it is directed to the purchase of automotive and after it reaches a greater value to the purchase of real estate. Because it is not possible to expect the development of mortgage loan financing systems that provide long-term financing possibility from the money markets where short-term behaviour characteristics are predominate. In such a structure it is also unlikely to ensure the continuity of housing demand and supply. The regulation of the markets (the market maker), in which the products, which are developed to reduce the negativeness of this process, are traded, gains importance. In this study it is tried to give, besides the means to be developed, the evolution that will be provided by the regulation of the markets in which these means will be traded, and both how the mattress savings can be transferred to the economy and how the development of capital markets can be.